An anatomy of business model innovation in Latin America- a fuzzy extended analytic hierarchy process application - van Klyton, Aaron; Carbonell Garcia, Diego Fernando; Restrepo-Estrada, Camilo Ernesto (Journal of business research, 2026)
This study investigates how internal and external factors interact under conditions of complexity to shape business model innovation (BMI) in Latin America. While firms in emerging markets face growing pressure to innovate, they must do so within structurally volatile environments marked by institutional fragmentation, limited resources, and cultural resistance to failure. Existing literature on BMI often isolates internal and external drivers or assumes stable conditions typical of developed economies, leaving a gap in understanding how firms adapt to dynamic, interdependent constraints. Drawing on complexity theory—particularly concepts such as requisite variety, semiautonomous agency, and collaborative complexity—this study employs the Fuzzy Extended Analytic Hierarchy Process (FEAHP) to identify and prioritise 31 interrelated factors affecting BMI. Data were collected from Latin American innovation experts across multiple countries, yielding a regionally grounded hierarchy of strategic priorities. The results show that internal complexity—especially entrepreneurial orientation and organisational learning—forms the core of firms’ adaptive capacity, while collaborative complexity can only amplify innovation when these internal foundations are coherent. Fear of failure, hierarchical cultures, and fragmented learning systems emerged as key barriers. The study contributes to BMI and emerging market strategy literature by showing that firms in resource-constrained environments manage complexity not through discrete interventions, but through interdependent, evolving capabilities. Methodologically, it extends complexity theory through a hierarchical, evidence-based approach to factor prioritisation under uncertainty. Practically, it offers a structured framework to support firms and policymakers navigating innovation amid systemic turbulence.